Pengaruh Stres Kerja dan Motivasi terhadap Kinerja Melalui Kepuasan Kerja Perawat Rumah Sakit Pangeran Jaya Sumitra Kotabaru - Andriansyah Andriansyah; Irwansyah Irwansyah (JURNAL BISNIS DAN PEMBANGUNAN, 2022)
ABSTRACT The purpose of this study was to determine and examine the effect of work stress and motivation on performance through job satisfaction of nurses at Pangeran Jaya Sumitra Hospital, Kotabaru. Using a quantitative approach with explanatory type. The sample was selected as many as 107 nurses with use technique Simple Random Sampling Hypothesis testing using Partial Least Square (PLS).The results of this study indicate 1) there is a significant effect of work stress and motivation on nurse job satisfaction, 2) there is a significant effect of job stress, motivation, and job satisfaction on nurse performance. Indirectly motivation has a significant effect on nurse performance through job satisfaction, but job stress does not significantly affect nurse performance through job satisfaction.  Keywords: Job stress, motivation, job satisfaction, performance